ABDULLAH AVLONI IS A REPRESENTATIVE OF OUR NATIONAL CULTURE (Conference Zone, 2022)
Abdullah Avloni is an enlightened poet, playwright, journalist, scientist, statesman and public figure. The famous Uzbek enlightener, poet and public figure Abdulla Avloni was born on July 12, 1878 in Tashkent in a family of craftsmen. He was educated in the old school and studied in the madrasa. Due to financial difficulties in the family, he worked as a bricklayer, plasterer, baker, carpenter, builder, and was called a master builder.